Morphological and molecular identifcation of lymnaeid snail and trematodes cercariae in diferent water bodies in Perak, Malaysia - Ahmad Tookhy, Nazir; Md Isa, Nur Mahiza; Mansor, Rozaihan; Abd Rahaman, Yasmin; Ahmad, Nur Indah; Dung, Thi Bui; Idris, Lokman Hakim; Hamzah, Noor Hazfalinda; Zulkifli, Norhadila (Springer, 2023)
Lymnaeid snails play a crucial role in the transmission of trematode cercariae as an intermediate host that can infect humans, ruminants like buffalo, and other animals, resulting in serious economic losses. The purpose of the study was to identify the morphological and molecular characteristics of snails and cercariae collected from water bodies near buffalo farms that were integrated with palm oil in Perak, Malaysia. The presence or absence of snails in 35 water bodies was examined via cross-sectional study. From three marsh wetlands, 836 lymnaeid snails were gathered in total. Each snail’s shell was morphologically identified to determine its family and species. The cercarial stage inside each snail’s body was observed using the crushing method and trematode cercariae types were determined. In addition, the target gene Cytochrome c oxidase subunit 1 (Cox1) and the ribosomal internal transcribed spacer 2 (ITS2) region were used to identify the snail species and cercarial types according to the species level. The findings indicated that the collected snails belong to the family lymnaeidae and Radix rubiginosa species. In snails, the cercarial emergence infection rate was 8.7%. Echinostome, xiphidiocercariae, gymnocephalous, brevifurcate-apharyngeate distome cercariae (BADC), and longifurcate-pharyngeal monostome cercariae (LPMC) are the five morphological cercarial types that were observed. The cercariae were identified using morphological and molecular techniques, and they are members of the four families which are Echinostomatidae, Plagiorchiidae, Fasciolidae, and Schistosomatidae. Interestingly, this is the first study on R. rubiginosa and several trematode cercariae in Perak water bodies near buffalo farms that are integrated with palm oil. In conclusion, our research shown that a variety of parasitic trematodes in Perak use R. rubiginosa as an intermediate host.